2017
DOI: 10.1007/s12678-017-0395-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction Catalyzed by Small Gold Cluster on h-BN/Au(111) Support

Abstract: The catalytic activity for the oxygen reduction reaction (ORR) of a hexagonal boron nitride (h-BN) monolayer deposited on a Au(111) surface and decorated by a small planar Au 8 cluster has been studied theoretically using density-functional theory. It is shown that gold nanoparticles (Au-NP) deposited on the h-BN/Au(111) surface can provide catalytically active sites for effective ORR at the perimeter interface with the support. Stabilization of oxygen at the perimeter interface between Au-NP and h-BN/Au(111) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 96 publications
(121 reference statements)
1
17
0
Order By: Relevance
“…We find that the donor dopants F and Al significantly increase the negative charge on Au 20 to −3.96e and −3.97e, respectively, whereas the acceptor dopant N reduces it to −0.65e. The enhancement of negative charge is interesting, as there are several chemical reactions for which it is desirable that the Au nanocatalyst have a high negative charge; [22][23][24]30,31 this result has also been demonstrated by previous authors. 27,59,61 The novel result that we obtain here is that two of the acceptor dopants, viz., Na and Li, are able to make Au 20 acquire a positive charge: +0.42e and +0.49e, respectively.…”
Section: Au 20 On Doped Mgo(001)supporting
confidence: 60%
See 1 more Smart Citation
“…We find that the donor dopants F and Al significantly increase the negative charge on Au 20 to −3.96e and −3.97e, respectively, whereas the acceptor dopant N reduces it to −0.65e. The enhancement of negative charge is interesting, as there are several chemical reactions for which it is desirable that the Au nanocatalyst have a high negative charge; [22][23][24]30,31 this result has also been demonstrated by previous authors. 27,59,61 The novel result that we obtain here is that two of the acceptor dopants, viz., Na and Li, are able to make Au 20 acquire a positive charge: +0.42e and +0.49e, respectively.…”
Section: Au 20 On Doped Mgo(001)supporting
confidence: 60%
“…For example, positively charged Au clusters bind more strongly to CO, [13][14][15][16][17] C 2 H 4 , 18 and H 2 19 and are better catalysts for the oxidation of peroxidase substrate 20 and the dissociation of water. 21 In contrast, negatively charged Au nanoparticles are preferable for O 2 dissociation, 17,22,23 which is a necessary step in various oxidation reactions, including the oxidation of CO to CO 2 [24][25][26][27] and NO to NO 2 . 28,29 They are also better catalysts for reactions such as methanol oxidation 30 and the oxidation of organic molecules such as propylene.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Elumalai and coworkers further reduced the overpotential ca. 50 mV by boron nitride nanosheet (BNNS) supported gold nanoparticles (Elumalai et al, 2016; Lyalin et al, 2017). In addition, BNNS with vacancy defect has been proved to be excellent support for SACs.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrated the inertness of pure BN and verified that the interaction between BN and the Au substrate is a major influencing factor, which is consistent with Uosaki's experiment and previous theoretical results. [ 187,188,192 ] A similar work has been conducted by Banks and co‐workers [ 237 ] For C‐based substrates, it was found that the ORR catalytic activity of 2D h‐BN was highly dependent on the C material and cover/mass ratio. The h‐BN modified screen‐printed graphite electrode (SPE) showed a better electrochemical response than the GC‐ and B‐doped diamond electrodes.…”
Section: Boron Nitride For Electrochemical Catalysismentioning
confidence: 73%
“…The ORR activity was further increased by modifying the Au 8 nanoclusters on the surface of h‐BN/Au(111). [ 188 ] In terms of energy, the existence of Au 8 nanoclusters could stabilize O 2 *, OH*, and O*, strongly promoting the dissociation of OOH*, and open the four‐electron pathway to form H 2 O. For the heterogeneous interface formed by the monolayer h‐BN covering the Ni(111) surface, the mixing of Ni d z 2 orbitals with N p z and B p z of BN significantly enhanced the adsorption of intermediates (O 2 *, OOH*, OH*, and O*) and promoted the dissociation of the product (H 2 O), thus changing the ORR catalytic inertia of h‐BN.…”
Section: Boron Nitride For Electrochemical Catalysismentioning
confidence: 99%